Insinuations in the Shocking News of Sayyed Hassan Nasrallah's Martyrdom: A Contrastive Analysis - Dhayef, Qasim Abbas; Hadi, Nahla Mahmoud (Researchparks Publishing, 2024)
This study conducts a contrastive analysis of the news surrounding the martyrdom of Sayyed Hassan Nasrallah, as reported in Arabic and English media. By examining selected headlines, the research highlights the differing thematic emphases and linguistic choices that shape public perception in each context. Utilizing a contrastive analysis model based on Gee (2014), the study identifies themes such as martyrdom, sacrifice, resistance, and vengeance. Thematic analysis, as outlined by Braun and Clarke (2006), reveals how these themes resonate differently with audiences, while linguistic analysis informed by Fairclough (1995) underscores the cultural significance of specific word choices. Furthermore, cultural contextualization is explored through Said's (1978) framework, emphasizing the role of cultural identity in shaping narratives. Qualitative interpretation, guided by Charmaz (2006), provides insights into how these contrasting portrayals reflect broader ideological divides and influence regional dynamics. The findings suggest that while Arabic narratives evoke deep emotional responses tied to loss and martyrdom, English narratives prioritize strategic implications and calls for retaliation. This study contributes to a nuanced understanding of how media representations of Nasrallah's death reflect divergent cultural values and political contexts, ultimately shaping public sentiment across different regions.